(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
The present pregression of the highly contagious novel coronavirus [COVID-19] has been testing the healthcare system globally pressing the medical staff everywhere. Present and future healthcare workers’ updated knowledge, proper attitude towards the pandemic and adequate preventive practices are of paramount importance for the combat effectiveness of the healthcare burden.This study assessed the knowledge, practice and attitudes regarding COVID-19 among the nursing students of a tertiary care center in Eastern India. KAP scores were compared with their socio-demographic variables. Inter-relation between knowledge, attitude and practice was also assessed.Out of the 131 students participated in the study the KAP parameters were not significantly different based on the socio-demographic factors. Though knowledge and attitude parameters were positively correlated among them, it was found that practice was negatively correlated to both knowledge and attitude. This finding can be attributed to them being non-exposed and inexperienced in the regular healthcare activities as well to the fact that Indian population was to some extent unprepared to cope up with this type of epidemic for a long time. Training on the updated knowledge along with exposure to simulated environment with scheduled supervision to reflect the behavior of the students is of great importance so that in extreme situation, the trainee students can also come handy into utilization if needed.